2005
DOI: 10.1038/nature04190
|View full text |Cite
|
Sign up to set email alerts
|

Tunable gold catalysts for selective hydrocarbon oxidation under mild conditions

Abstract: Oxidation is an important method for the synthesis of chemical intermediates in the manufacture of high-tonnage commodities, high-value fine chemicals, agrochemicals and pharmaceuticals: but oxidations are often inefficient. The introduction of catalytic systems using oxygen from air is preferred for 'green' processing. Gold catalysis is now showing potential in selective redox processes, particularly for alcohol oxidation and the direct synthesis of hydrogen peroxide. However, a major challenge that persists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
692
0
11

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 985 publications
(721 citation statements)
references
References 22 publications
12
692
0
11
Order By: Relevance
“…This hydrocarbon oxidation has not been observed in the Pt-based catalyst although Au and Pd NPs supported on various supports are found to be effective catalysts for the oxidation of alcohols in the presence of oxidants. 58,59 To understand this unexpected oxidation in the hydrogen atmosphere over the Pt-CoFe 2 O 4 @meso-SiO 2 catalyst, a wide range of control experiments using compositionally modified catalysts were performed under the same conditions. The hydrogenation reaction was done with the CoFe 2 O 4 @meso-SiO 2 microsphere to check the catalytic activity of CoFe 2 O 4 NPs, which was almost insensitive to the hydrogenation reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This hydrocarbon oxidation has not been observed in the Pt-based catalyst although Au and Pd NPs supported on various supports are found to be effective catalysts for the oxidation of alcohols in the presence of oxidants. 58,59 To understand this unexpected oxidation in the hydrogen atmosphere over the Pt-CoFe 2 O 4 @meso-SiO 2 catalyst, a wide range of control experiments using compositionally modified catalysts were performed under the same conditions. The hydrogenation reaction was done with the CoFe 2 O 4 @meso-SiO 2 microsphere to check the catalytic activity of CoFe 2 O 4 NPs, which was almost insensitive to the hydrogenation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…[51][52][53][54][55] Gold NPs supported on metal oxides are known to be highly efficient for the oxidation reactions under relatively mild conditions. 56,57 In particular, Hughes et al reported that supported Au catalysts are very effective for the oxidation of cyclohexene in the presence of molecular oxidant although they require temperatures above 80 o C. 58 More recently, Enache et al revealed that Au-Pd catalysts supported on TiO 2 provide exceptionally high turn-over frequencies for the oxidation of alcohols in which the addition of gold to palladium increases the selectivity. 59 These studies have triggered new interest in the development of oxidation catalysts on the basis of active metals supported on various solid oxides.…”
Section: Introductionmentioning
confidence: 99%
“…45 The need to adeptly design specific active sites is already wellestablished within nanoparticle chemistry; where intrinsic compositional control at the nanoscale coupled with tuning the size-and shape-of the metal nanoparticles, ensues the origin of discrete single-sites that are catalytically active and selective (see Table 3). [50][51][52] A wide-range of synthetic strategies 53 have been recently evolved to generate metal nanoparticles with innate control on morphology and particle size. One such method involves the introduction of carbonyl-capped metalnanoclusters to solid (typically siliceous) supports to form particles of specific sizes and molecularity.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocatalysis is an important part of nanoscience, materials science and chemistry [1][2][3][4]. Many nanoparticles have been used to catalyze a variety of chemical reactions.…”
Section: Introductionmentioning
confidence: 99%